Pengembalian Modal Usaha Program Komunitas Usaha Mikro Muamalat Berbasis Masjid Kota Bogor - Kostia Digdaha; Rizal Syarief; MH Bintoro Djoefrie (Institut Pertanian Bogor, 2016)
In the process of eradicating poverty, Bank Muamalat with the collaboration with the Baitul Maal Muamalat (BMM), has undertaken the Mosque Based Micro Muamalat Community Program (KUM3). The problem identified in the program is that many members of KUM3 cannot make a capital return at the right time, causing them to fail in re-threading the capital. This study aims to determine the factors that affect the KUM3 member’s capital returns. Investigations carried out in four districts in Bogor City namely the Community of Loji, Pamoyanan, Pasar Anyar and Situ Gede. Eight factors that might affect the business capital was studied i.e. the value of social capital, the theory, the economy, the religion, marketing, finance, management and technical. The method used in analysing the data is the multiple logistic model . The analysis obtained a good results in the social value, theoretical value, the economy, the religion, marketing, finance, management , and technical for the KUM3 participants in Bogor City. The most influential factor in the return of capital is the social value. Two factors were studied in this value i.e. family factor and community factor. It has a tendency to break on time 6.46 times faster with the value of the regression coefficient 1.946 and value of -p 0.010 (<0.05) compared to the social disadvantage significance level of 5% . The good social value has a tendency to break even at 7,000 times compared to the less good social value. Based on the comparison between the family factor and the community factor, both have an impact on the capital returns